Relasi Fiqh Muamalat dengan Ekonomi Islam - Zainil Ghulam (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2016)
Association of human society, will lead to personal interests for the sake of self-sufficient. From this will be born the rights and obligations that must be observed as a result of the fulfillment of human life necessities. Every human being bears the rights and obligations of each. Therefore, the association's rights and obligations should be regulated in accordance with the law and order that is clearly not harm each other. For example, every human being must be in need of property or the property of others. To meet these needs, the emerging practice of barter (exchange of goods), then buying and selling directly and are now developing more advanced such as e-commerce. Practices such as these need standards clear law to protect the rights and obligations of each. From here, the Muslim scholars to formulate diligence